2023
DOI: 10.1159/000530168
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cognitive Impairment in Peritoneal Dialysis Patients and Associated Factors

Abstract: Background. Cognitive impairment (CI) in patients with chronic kidney disease, including those treated with renal replacement therapy (RRT) is a growing problem worldwide. The study aimed to assess the prevalence of CI and associated factors in patients undergoing peritoneal dialysis (PD). Methods. In this cross-sectional study, 18 consecutive patients with PD therapy and 15 controls were evaluated for CI using the Addenbrooke's Cognitive Examination III (ACE III) test. Results. The prevalence of CI was 33% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…patients with ESKD demonstrated problems in tests assessing executive function in the first months of RRT, while there were no difficulties in general cognitive skills [ 27 ]. Furthermore, a few studies, assessing cognitive abilities in CKD patients, including our previously published study, found verbal fluency to be the most affected domain, which reflects executive dysfunction [ 3 , 4 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…patients with ESKD demonstrated problems in tests assessing executive function in the first months of RRT, while there were no difficulties in general cognitive skills [ 27 ]. Furthermore, a few studies, assessing cognitive abilities in CKD patients, including our previously published study, found verbal fluency to be the most affected domain, which reflects executive dysfunction [ 3 , 4 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Age is also a strong predictor of cognitive dysfunction. The prevalence of CI in patients on RRT is higher than in CKD patients and is highest in hemodialysis patients (HD) in comparison to peritoneal dialysis (PD) and kidney transplant recipients [ 3–5 ]. On the other hand, the prevalence of CI may be underestimated due to the exclusion of patients with severe disabilities such as vision and hearing problems, language and movement disorders, language barrier, as well as patients who refused to participate in the cognitive assessment [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidney transplantation (KT) is the treatment of choice for most patients with end-stage kidney disease to increase survival and quality of life [ 1 ]. Cognitive impairment (CI) is common in hemodialysis and peritoneal dialysis patients [ 2 , 3 ] and may also be detected in kidney transplant candidates [ 4 ]. CI prior to KT is associated with a lower likelihood of being listed for transplant and with a longer waitlist for transplantation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%